High-Performance Visible-Blind UV Phototransistors Based on n-Type Naphthalene Diimide Nanomaterials - Song, Inho; Lee, Seung Chul; Shang, Xiaobo; Ahn, Jaeyong; Jung, Hoon Joo; Jeong, Chan Uk; Kim, Sang Wook; Yoon, Woojin; Yun, Hoseop; Kwon, O. Pil; Oh, Joon Hak (ACS Applied Materials and Interfaces, 2018)
This study investigates the performance of single-crystalline nanomaterials of wide-band gap naphthalene diimide (NDI) derivatives with methylene-bridged aromatic side chains. Such materials are found to be easily used as high-performance, visible-blind near-UV light detectors. NDI single-crystalline nanoribbons are assembled using a simple solution-based process (without solvent-inclusion problems), which is then applied to organic phototransistors (OPTs). Such OPTs exhibit excellent n-channel transistor characteristics, including an average electron mobility of 1.7 cm2 V-1 s-1, sensitive UV detection properties with a detection limit of ∼1 μW cm-2, millisecond-level responses, and detectivity as high as 1015 Jones, demonstrating the highly sensitive organic visible-blind UV detectors. The high performance of our OPTs originates from the large face-to-face π-π stacking area between the NDI semiconducting cores, which is facilitated by methylene-bridged aromatic side chains. Interestingly, NDI-based nanoribbon OPTs exhibit a distinct visible-blind near-UV detection with an identical detection limit, even under intense visible light illumination (for example, 104 times higher intensity than UV light intensity). Our findings demonstrate that wide-band gap NDI-based nanomaterials are highly promising for developing high-performance visible-blind UV photodetectors. Such photodetectors could potentially be used for various applications including environmental and health-monitoring systems.
Keywords: Aromatic side chains; Health monitoring system; N-channel transistors; Naphthalene diimide; Organic phototransistors; Single-crystalline; Solution-based process; UV light intensity